The Influence of Information Technology Capability and Knowledge Management on Competitive Advantage Through Innovation as an Intervening Variable (Study on Traditional Riau Food SME’s in Pekanbaru) - Putri Balqis; Samsir; Prima Andreas Siregar; Rio J.M. Marpaung (urn:multiple://2988-7828multiple.v3i24)
The increasing competition in the business sector, particularly among SMEs in Indonesia, requires enterprises to leverage technology and knowledge management to enhance their competitive advantage. This study aims to analyze the influence of information technology capability and knowledge management on competitive advantage, with innovation as an intervening variable in traditional Riau food SMEs in Pekanbaru City. The research employs Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach, utilizing SmartPLS software version 4.1.0.9 for data processing. Data were collected through surveys distributed to SME owners and managers. The findings reveal that innovation significantly enhances competitive advantage, while information technology capability does not directly impact competitive advantage but positively influences innovation. Moreover, knowledge management has a significant positive effect on both innovation and competitive advantage. Additionally, innovation acts as a mediator in the relationship between information technology capability, knowledge management, and competitive advantage. These results highlight the critical role of innovation in strengthening SME competitiveness and emphasize knowledge management as a key driver of innovation. The study suggests that SMEs should optimize technology utilization to support innovation and improve market positioning. This research provides valuable insights for SME practitioners and policymakers in developing strategies to enhance competitiveness through innovation and knowledge management.